Curriculum Development in the Thematic Learning Process Through Management Information Systems at TK Aisyiyah Bustanul Athfal Jatibarang - Wiwik Hidayati; Tri Joko Raharjo; Joko Sutarto; Titi Prihati (International Conference on Science, Education, and Technology, 2023)
Learning is an interactive process between students and educators and learning resources in a learning environment. Topic learning is a learning model that emphasizes the importance of developing students holistically. Educators are used to teaching models of certain subjects, but have not yet reached the optimal point. The need to improve the quality of teachers to implement subject-specific learning models that are in line with the applied curriculum. This study aims to achieve how the development of the curriculum together with thematic learning efforts through management information systems in TK Aisyiyah Bustanul Athfal Jatibarang. This study was conducted at TK Aisyiyah Bustanul Athfal Jatibarang. This research is qualitative research. Research studies that are technical in nature and tend to be analysis-based. Early Childhood Education Development Information System Research in TK Aisyiyah Bustanul Athfal Jatibarang is an academic system for recording, processing, storing, reporting and informing data and information. This phase discusses learning approaches, learning strategies and tactical aspects, learning methods and technical aspects. Learning media used in the learning process are print media (books), photos, LCDs and computers. Third, there is the evaluation stage. In this phase, the acquired knowledge is evaluated, which is checked against a list of written, oral and exam questions. Learning ability is assessed through practical skills tests and task analysis that educators self-assess. And the exam format for students must still meet the standard requirements. The results of this study are expected to find out how the development of the curriculum in the thematic learning process through the management information system at TK Aisyiyah Bustanul Athfal Jatibarang.